The Association between Toll-like Receptor 7 and Hepatitis C Virus in a Sample of Iraqi Rheumatoid Arthritis Patients - Dunya Muyad Ahmed (Journal of Global Pharma Technology, 2018)
Background: Rheumatoid arthritis (RA) is one of the chronic inflammatory autoimmune diseases that included articular and joints infections. Viral infection and immunity had been suggested to play a role in the pathogenesis of autoimmune diseases. Objectives: The present study designed to estimate the association among RA, Hepatitis C virus (HCV) infections and the role of innate immunity expressed by toll-like receptor-7 (TLR-7) as a possible triggering factor in the sera and blood samples of 47 RA patients. Results: The findings of the present study demonstrated that 18 of the 47th RA samples were positive for anti-HCV IgM and IgG antibodies, and 13 of the 18th HCV IgG and IgM seropositive samples were positive for HCV-RNA by using RT-PCR technique. Also, the findings revealed a significant association between RA, HCV infections and TLR-7 serum level in the studied groups. There was a significantly increased level of TLR-7 in the RA group (103.0±73.8 ng/ml) compared to controls (72.9±36.8 ng/ml). Conclusion: These findings concluded that hepatitis C virus infection and TLR-7 might have a role in RA pathogenesis.Keywords: Autoimmune disease, Rheumatoid arthritis, Hepatitis C virus, Innate immunity, Toll-like receptor-7.